Pemanfaatan Media Sosial dan Pangan Lokal menuju Ketahanan Pangan Berwawasan Lingkungan pada Kegiatan Posyandu - Prasetyani, Henny; Hidayat, Umar; Rifandi, Raditya Ahmad (Lembaga Dongan Dosen, 2024)
Social media provides information that can increase knowledge about stunting and nutrition. Another problem is that in providing PMT, local food is still not utilized, even though parents can provide local food to toddlers to fulfill nutrition to prevent stunting. The provision of PMT carried out by Posyandu is still in the form of packaged food/drinks, even though the provision of PMT in the form of packaged food should be avoided because of its low nutritional content. Then the use of social media as a tool to disseminate information and local food to be utilized in fulfilling toddler nutrition can be used to move towards environmentally friendly food security. The goal is to improve services by utilizing social media applications and local food. Social media applications aim to disseminate information related to nutrition and stunting through content. Local food is used to fulfill nutrition, especially in providing PMT at Posyandu. The use of these two aspects is expected to realize food security, which is supported by the creation of a greenhouse that will cultivate plants to fulfill nutrition. Then by realizing food security, it will also support the environment by making natural fertilizers with eco enzymes. The results of natural fertilizers can be used for plant fertilizers in the greenhouse. The stages of implementing nutritional education services are: (1) utilization of social media to disseminate information; (2) utilization of local food in fulfilling toddler nutrition; and (3) implementing good management to achieve environmentally conscious food security as a form of helping integrated health post service facilities.